Analisis Faktor Penyebab Stres pada Mahasiswa dan Dampaknya terhadap Kesehatan Mental - An Al Rivaldi (Pusat Riset dan Inovasi Nasional, 2024)
Stress is a common phenomenon experienced by university students due to academic and social pressures in the campus environment. This study aims to analyze the factors causing stress among students and its impact on their mental health. Using a phenomenological approach, data were collected through in-depth interviews and field observations with students from various backgrounds. The findings reveal that factors such as academic workload, adaptation to new environments, financial issues, and social pressures are primary sources of stress. This stress can lead to mental health issues, including anxiety, depression, and reduced academic performance. The study highlights the importance of campus interventions in providing mental support and developing stress management programs for students. With this understanding, students are expected to better manage stress, maintain mental balance, and improve their quality of life in academic settings.